2021
DOI: 10.1101/2021.02.24.432210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stratification of Chemotherapy-Treated Stage III Colorectal Cancer Patients Using Multiplexed Imaging and Single Cell Analysis of T Cell Populations

Abstract: Colorectal cancer (CRC) has one of the highest cancer incidences and mortality rates. In stage III, postoperative chemotherapy benefits <20% of patients, while more than 50% will develop distant metastases. Predictive biomarkers for identification of patients with increased risk for disease recurrence are currently lacking, with progress in biomarker discovery hindered by the inherent heterogeneity of the disease. The immune profile of colorectal tumors has previously been found to have prognostic value. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Our comparatively small sample size is explained by the specificity of the population targeted by our study, and is similar to the sample size of other surveys recently published on this particular population 35,36 . However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our comparatively small sample size is explained by the specificity of the population targeted by our study, and is similar to the sample size of other surveys recently published on this particular population 35,36 . However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Discussionmentioning
confidence: 52%
“…Heeg et al 34 population. 35,36 However, our restrictive selection criteria had the advantage of providing a homogenous sample, which limits potential confounding bias.…”
Section: Weaknesses and Strengths Of This Studymentioning
confidence: 99%
“…The fact that previous studies suggested a positive association between regulatory T-cells and worse outcome [39] should be interpreted taking into account differences in the clinical characteristics of the cohorts studied and the methods used to quantify regulatory T-cells. Further, one study analyzing chemotherapy-treated stage III colorectal carcinomas found improved outcomes for regulatory T-cell tumors [40].…”
Section: Discussionmentioning
confidence: 99%